Breaking into New Markets, Raising Quality, and Improving Services : Neglected Avenues for Export Diversification - Brenton, Paul; Walkenhorst, Peter (World Bank, Washington, DC, 2012)
Expanding international trade is an important avenue for growth and development in low-income countries. In addition to increasing the quantity of existing export flows, many countries seek to diversify into production and export activities that provide a higher return to the labor and capital resources employed. Export diversity also reduces a country's vulnerability to pronounced price swings in international markets. This note reviews the findings of a series of papers on the diversification process contained in Newfarmer, Shaw, and Walkenhorst (2009). The analysis suggests that there has been too much focus on simply adding new products to export portfolios, which often underscores the use of industrial policies. While such actions are important, a more comprehensive view of diversification, and hence a more comprehensive trade policy, is needed that improves the quality of existing exports, breaks into new geographic markets, and increases services exports.